2011
DOI: 10.1186/1749-8090-6-143
|View full text |Cite
|
Sign up to set email alerts
|

Acute pressure overload of the right ventricle. Comparison of two models of right-left shunt. Pulmonary artery to left atrium and right atrium to left atrium: experimental study

Abstract: AbtractBackgroundIn right ventricular failure (RVF), an interatrial shunt can relieve symptoms of severe pulmonary hypertension by reducing right ventricular preload and increasing systemic flow. Using a pig model to determine if a pulmonary artery - left atrium shunt (PA-LA) is better than a right atrial - left atrial shunt (RA-LA), we compared the hemodynamic effects and blood gases between the two shunts.MethodsThirty, male Large White pigs weighting in average 21.3 kg ± 0.7 (SEM) were divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This can be accomplished via pulmonary artery-left atrial graft and has been shown to improve RV function. 29,30 Intraoperative echocardiography is used to assess biventricular and valvular function, presence of shunts, and detection of cardiac thrombi. Adequate pump function should be confirmed at this time, and if cardiac index is < 2.0 and central venous pressure is > 20, a temporary RVAD should be considered.…”
Section: Surgical Managementmentioning
confidence: 99%
“…This can be accomplished via pulmonary artery-left atrial graft and has been shown to improve RV function. 29,30 Intraoperative echocardiography is used to assess biventricular and valvular function, presence of shunts, and detection of cardiac thrombi. Adequate pump function should be confirmed at this time, and if cardiac index is < 2.0 and central venous pressure is > 20, a temporary RVAD should be considered.…”
Section: Surgical Managementmentioning
confidence: 99%
“…A worsening TR, due to the shift of IVS with a dilated tricuspid annulus, may need correction, as this will help in maintaining venous flow and renal perfusion and significantly reduces post-operative morbidity. There are sporadic reports indicating that creation of a PA to LA shunt helps in reducing the RV after-load and improves function [48,49]. Intraoperatively, RV failure is recognized when the cardiac index (CI) remains than 2.0 L/min/m 2 and CVP is greater than 20 mmHg.…”
Section: Iv) Pulmonary Artery Pulsatility Index (Papi)mentioning
confidence: 99%
“…Pulmonary artery-left atrium shunt has been proposed and preferred to an inter-atrial shunt to moderate or even partially reverse the adverse effects of acute right ventricle pressure overload [56]. Finally, atrial fibrillation is common after lung transplantation despite the absence of graft rejection and cardiac dysfunction [57].…”
Section: Pulmonary Hypertension Pulmonary Wedge Pressure and Right Vmentioning
confidence: 99%